P-023 Transfontanelle and Transcardiac Veno-arterial Approaches for Embolization of Complex Pediatric Intra-cranial Vascular Malformations. (26th July 2014) - Jagadeesan, B; Zachararotos, H; Shea, K; Nascene, D; Grande, A; Tummala, R
Abstract : Introduction: Trans-arterial endovascular embolization using liquid embolics for the treatment of intra-cranial vascular lesions can be challenging in neonates and infants due to difficulties with arterial access. This is particularly true when repeated procedures have to be performed for staged embolization of very complex lesions. Sometimes, there can be severe intra-procedural spasm or long standing occlusion of the femoral arteries, which can render arterial access very difficult. A Transvenous approach may also not be useful due to the angio-architecture of some of these lesions. Herein, we describe two patients in whom arterial access was compromised but embolization could still be carried out via alternate techniques. Case Series: Case 1: A 2 week old infant presented with a Dural Sinus Malformation and a giant midline venous pouch, with multiple associated high flow arteriovenous fistulae. At the end of six trans-arterial embolization sessions with femoral arterial punctures, she still had residual high flow shunting. Both femoral arteries were small in calibre and the left was occluded. Therefore, the midline venous pouch was punctured via a percutaneous transfontanelle approach (through the posterior fontanelle) and the malformation was successfully embolised using Ethylene Vinyl Alcohol Co-polymer (Onyx) and coils while preserving the superior saggital sinus. Case 2: A 5 month old presented for elective embolization of an antenatally diagnosed mixed mural and choroidal type Vein of Galen Aneurysmal Malformation (VGAM). Both femoral arteries were small in size and developed severe vasospasm when an ultra-sound guided needle puncture was attempted precluding arterial access by this approach. Therefore, the right common femoral vein (CFV) was punctured under ultrasound and a 4 French Guiding catheter was passed through this puncture site and advanced to the right atrium. Eventually arterial access was obtained by navigating this catheter from the right atrium to the left atrium across the patent Foramen Ovale followed by advancement into the aortic arch. Embolization was then carried out successfully by the injection of Onyx or n-BCA from multiple pericallosal and choroidal arteries with approximately 50% reduction in flow through the VGAM. Conclusion: Per-cutaneous Transfontanlle and Trans-cardiac percutaneous veno-arterial approaches for embolization may be useful in the treatment of selected intra-cranial vascular malformations in neonates and infants. Disclosures: B. Jagadeesan: 2; C; Covidien, Microvention, Lake Regional. H. Zachararotos: None. K. Shea: None. D. Nascene: None. A. Grande: 2; C; Covidien, Integra. R. Tummala: 2; C; Lake Regional.